Alterations in the health of hibernating bats under pathogen pressure - Bandouchova, Hana; Bartonička, Tomáš; Berkova, Hana; Brichta, Jiri; Kokurewicz, Tomasz; Kovacova, Veronika; Linhart, Petr; Piacek, Vladimir; Pikula, Jiri; Zahradníková, Alexandra; Zukal, Jan (Scientific reports, 2018)
In underground hibernacula temperate northern hemisphere bats are exposed to Pseudogymnoascus destructans, the fungal agent of white-nose syndrome. While pathological and epidemiological data suggest that Palearctic bats tolerate this infection, we lack knowledge about bat health under pathogen pressure. Here we report blood profiles, along with body mass index (BMI), infection intensity and hibernation temperature, in greater mouse-eared bats (Myotis myotis). We sampled three European hibernacula that differ in geomorphology and microclimatic conditions. Skin lesion counts differed between contralateral wings of a bat, suggesting variable exposure to the fungus. Analysis of blood parameters suggests a threshold of ca. 300 skin lesions on both wings, combined with poor hibernation conditions, may distinguish healthy bats from those with homeostatic disruption. Physiological effects manifested as mild metabolic acidosis, decreased glucose and peripheral blood eosinophilia which were strongly locality-dependent. Hibernating bats displaying blood homeostasis disruption had 2 °C lower body surface temperatures. A shallow BMI loss slope with increasing pathogen load suggested a high degree of infection tolerance. European greater mouse-eared bats generally survive P. destructans invasion, despite some health deterioration at higher infection intensities (dependant on hibernation conditions). Conservation measures should minimise additional stressors to conserve constrained body reserves of bats during hibernation.
Keywords: Hibernation; mykózy; Ascomycota; Mycoses; index tělesné hmotnosti; kožní nemoci; Animals; Chiroptera; zvířata; Body Mass Index; Host-Pathogen Interactions; hibernace; Skin Diseases; interakce hostitele a patogenu